Financing affordable housing in Yangon. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
Myanmar housing sector is struggling to cope with rapid urbanization, internal migration, and new demand arising from recent economic growth. These challenges are most apparent in the Yangon Region, where estimates suggest there will be a housing shortage of 1.3 million units by 2030. After assessing the current housing market situation in Yangon, the publication identifies reform options and offers practical recommendations.
Keywords: Housing policy -- Myanmar; Housing -- Finance -- Government policy -- Myanmar; Electronic book